Research data governance activities for implementation in Malaysia research performing organizations: insights from data practitioners via Delphi study - Hazmi, Norzelatun Rodhiah; Abdullah, Abrizah; Mohd Khalid, Yanti Idaya Aspura (Universiti Malaya, 2023)
Therapidgrowthofresearchdataanditsinfluenceonresearchpracticeshasheightenedglobalawarenessofthesignificanceofresearchdatagovernance(RDG).However,thereisalackofliteratureexplicitlyoutliningtheimplementationofRDGandthepracticesadoptedbyresearchperformingorganizations(RPOs).Thisstudyintendstobridgethisgapbyutilizingathree-roundmodifiedDelphimethod,whichinvolvesasystematicsolicitationandcollectionoffeedbackfromapoolofexpertscomprisingresearchdatapractitioners.ThisisaccomplishedthroughaseriesofcarefullydesignedsequentialsurveysfocusedexplicitlyonRDGactivitiesconcerningtasksassociatedwithgovernanceroles,areasanddecisiondomainswithinRPOsinMalaysia.TheobjectiveofthisstudyistodevelopconsensusamongresearchdatapractitionersontheimportanceofRDGactivities.Statementswereevaluatedusinga5-pointscale,andconsensuswasdeterminedasaninterquartiledeviation(IQD)≤0.5,amedian≥4,andaconsensuslevel(CL)≥85%.Analysisoftheresponsesrevealedasignificantconsensusamongtheexpertson106outof119RDGtaskstatementsonvariousroles,nineteenareas,andeightdecisiondomainsdeemedsignificanttotheRDGimplementationwithinRPOs.ThisstudycanpotentiallydevelopanRDGframeworkbasedontheconsensusachieved.ByprovidinganRDGframeworkthatcanbeusedasasetofbestpractices,thisstudycanassistRPOleadersinconsideringimplementingRDGanditseffortsintheirorganizations.